2016
DOI: 10.1021/acs.jced.6b00607
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ice in Confinement: Water in Mesoporous Carbons

Abstract: In this study, the structure of nanoconfined ice and its behavior during the melting process have been investigated. For this purpose, deionized water was inserted into the pores of the ordered carbon structures CMK-3 and CMK-8 having pores of different diameters. The first set of experiments was performed using differential scanning calorimetry (DSC), from which the melting transition temperature of the confined ice was determined. In order to investigate the structure of ice formed inside the mesopores, wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
(80 reference statements)
4
12
0
1
Order By: Relevance
“…Ice confined in nanopores becomes more cubic as the pore size decreases [14,15]. A similar dependence was shown by Domin et al [55]; when water is confined in smaller pores, the calculated percentage composition of the cubic form of ice increases. Malkin et al [38] showed that the ice produced from homogeneous nucleation in pure water droplets at around 230 K was fully random, with 50% cubic and 50% hexagonal stackins.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Ice confined in nanopores becomes more cubic as the pore size decreases [14,15]. A similar dependence was shown by Domin et al [55]; when water is confined in smaller pores, the calculated percentage composition of the cubic form of ice increases. Malkin et al [38] showed that the ice produced from homogeneous nucleation in pure water droplets at around 230 K was fully random, with 50% cubic and 50% hexagonal stackins.…”
Section: Resultssupporting
confidence: 81%
“…Such a defective structure of the cubic ice was also observed in previous experiments on confined ice formation [15,18,25]. Recently published results of X-ray diffraction studies for water confined in nanopores [55,56] and the theoretical studies by Malkin et al [31,38] suggest that the obtained profile can be a hybrid of both hexagonal and cubic ice forms that were formed as a result of stacking faults. The theory [38] predicts that when a water droplet freezes, a two-dimensional nucleation process occurs.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…48 The second branch, at 10 −6 s, appears immediately below the pore melting point and can be related to the cubic I c form of ice confined in the pores. 48 As follows from the recent work of Domin et al, 49,50 the metastable ice formed in pores is a combination of cubic sequences intertwined with hexagonal sequences stabilized by the confinement. The theory 51 predicts that when a water droplet freezes, a two-dimensional nucleation process occurs.…”
Section: Resultsmentioning
confidence: 87%
“…The results are reported in Table 1. These data should only be considered as tentative guidelines, as it is known that confinement in pores alters the thermodynamic properties of fluids [37][38][39][40]. In particular, extended Peng-Robinson equations of state have been used to predict fluid behaviour in cylindrical and slit pores [41][42][43].…”
Section: Simulation Set Upmentioning
confidence: 99%